Angiogenic and molecular diversity determine hepatic melanoma metastasis and response to anti-angiogenic treatment - Wohlfeil, Sebastian A.; Häfele, Verena; Dietsch, Bianca; Weller, Céline; Sticht, Carsten; Jauch, Anna Sophia; Winkler, Manuel; Schmid, Christian David; Irkens, Anna Lena; Olsavszky, Ana; Schledzewski, Kai; Reiners-Koch, Philipp-Sebastian; et al. (Journal of translational medicine, 2022)
BACKGROUND: Cutaneous melanoma exhibits heterogeneous metastatic patterns and prognosis. In this regard, liver metastasis, which is detected in ~ 10-20% of stage 4 patients, came to the fore of melanoma research, as it recently evolved as decisive indicator of treatment resistance to immune checkpoint inhibition. - METHODS: Hepatic metastases were induced by intrasplenic injection of five different murine melanoma cell lines. The efficiencies of hepatic colonization, morphologic patterns, gene expression profiles and degree of vascularization were analyzed and Sorafenib was applied as anti-angiogenic treatment. - RESULTS: WT31 melanoma showed the highest efficiency of hepatic colonization, while intermediate efficiencies were observed for B16F10 and RET, and low efficiencies for D4M and HCmel12. RNAseq-based gene expression profiles of high and intermediate metastatic melanomas in comparison to low metastatic melanomas indicated that this efficiency predominantly associates with gene clusters involved in cell migration and angiogenesis. Indeed, heterogeneous vascularization patterns were found in the five models. Although the degree of vascularization of WT31 and B16F10 metastases differed, both showed a strong response to Sorafenib with a successful abrogation of the vascularization. - CONCLUSION: Our data indicate that molecular heterogeneity of melanomas can be associated with phenotypic and prognostic features of hepatic metastasis paving the way for organ-specific anti-angiogenic therapeutic approaches.
Gesehen am 07.02.2022